Persepsi Mahasiswa Terhadap Penggunaan Fitur Foto Dalam Google Translate Untuk Pembelajaran Bahasa Jepang: Case Study - Satriatama, Prasetya Eghy; Rasiban, Linna Meilia; Juangsih, Juju (Vocational College of Diponegoro University, 2024)
Google Translate is one of the most popular translation applications today. This application is widely used by the community, one of which is among students who study foreign languages. One of the most frequently used features is the photo feature on Google Translate. In order to improve the quality of Japanese language learning at Semarang State University, this research will be carried out to explore the use of modern technology, especially the photo feature in Google Translate, as a potential tool in Japanese language education. The purpose of this study is to identify the extent to which students use this technology in the environment of Japanese Language Education students at this university. In addition, this study aims to analyze students' views on the effectiveness and usefulness of this feature in assisting their understanding and mastery of Japanese. The research method used is descriptive research method with a quantitative approach. This article will also present the results of an opinion survey of the students who were the subjects of the study. The results of the survey will be interpreted to provide a better understanding of how the student uses the photo features in Google Translation in their English language learning process.